2005
DOI: 10.1111/j.1439-0507.2005.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chrysosporium keratinophillum in the parasitic evolution of dermatophytes

Abstract: Anti-dermatophytic activity of Chrysosporium keratinophillum against species of the genera Trichophyton, Microsporum and Epidermophyton floccosum was tested in vitro. When C. keratinophillum and different species of dermatophytes were inoculated on Sabouraud's dextrose agar plates 2 cm apart, no antagonistic effect of C. keratinophillum on the mycelial growth of dermatophytes was observed. However, conidia production was not observed on the hyphae of Trichophyton rubrum, Trichophyton tonsurans and E. floccosum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Considering the global prevalence of Chrysosporium spp. and in combination with the results in the present study, it is speculated whether the antidermatophytic activity of these fungi might also be one of the early events for the evolutionary divergence of some geophilic archi-dermatophyte (saprophytic) to obligate parasitic dermatophyte species (Gokulshankar et al, 2005). The antibiosis of other soil microbes on dermatophytes also cannot be underestimated for such a parasitic evolution of dermatophytes.…”
Section: T Ajelloi T Terrestre)mentioning
confidence: 62%
See 3 more Smart Citations
“…Considering the global prevalence of Chrysosporium spp. and in combination with the results in the present study, it is speculated whether the antidermatophytic activity of these fungi might also be one of the early events for the evolutionary divergence of some geophilic archi-dermatophyte (saprophytic) to obligate parasitic dermatophyte species (Gokulshankar et al, 2005). The antibiosis of other soil microbes on dermatophytes also cannot be underestimated for such a parasitic evolution of dermatophytes.…”
Section: T Ajelloi T Terrestre)mentioning
confidence: 62%
“…However, the viability of these organisms at least in sterilized soil for a prolonged period cannot be ruled out. The inability to recover these dermatophytes even by plating technique from the sterilized soil when they were inoculated along with C. keratinophillum (Gokulshankar et al, 2005) strongly suggests the possibility of SS released by C. keratinophillum has a definite role in the complete elimination of the dermatophytes. Interestingly, the growth of M. gypseum was not affected by SS produced by C. keratinophillum.…”
Section: T Ajelloi T Terrestre)mentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, C. keratinophilum inhibited T. rubrum, Trichophyton tonsurum and T. mentagrophytes, but not M. gypseum and Microsporum nanum. Gokulshankar et al [19] also studied the influence of Chrysosporium species on prevalence of dermatophytes in soil, whereas Tariq and Campbell [20] demonstrated influence of volatile metabolites of Geotrichum on some soil fungi. Ulfig [21] demonstrated that keratinophilic fungi unable to decompose hair exerted larger inhibitory effect on pathogenic dermatophytes in which T. mentagrophytes and Microsporum persicolor were more sensitive.…”
Section: Discussionmentioning
confidence: 99%